VD_FINDINFO HC / 2014 / 875 vom 31. Oktober 2014 - VD Tribunal cantonal (2014)
BAIL À LOYER, TRAVAUX D'ENTRETIENEN GÉNÉRAL, SOMMATION, INTERDICTION DE L'ARBITRAIRE, FARDEAU DE LA PREUVE | 8 CC, 320 CPC (CH), 322 al. 1 CPC (CH)